Social and Economic Conditions of Rice Farmers in Ngrandu Village Ponorogo Regency in 2000-2024: Kondisi Sosial Ekonomi Petani Padi - Mahmudi, Agus Rahmat (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The purpose of this study is to analyze the social and economic life of farmers in Ngrandu Village in 2000-2024 and analyze the development of agriculture in Ngrandu Village in 2000-2024. This study uses historical research methods which include: Heuristics, Criticism, Interpretation, and Historiography. The results of this study are: Getting to know Ngrandu Village, Ponorogo Regency, The development of agriculture, especially rice farming in Ngrandu Village has changed in 2000-2024, the social conditions of rice farmers in Ngrandu Village have changed in 2000-2024, the economic conditions of rice farmers in Ngrandu Village have changed in 2000-2024. Thus it can be seen that rice farmers in Ngrandu Village have changed from time to time.